Azaga = Postrimería? - Zuazo, Koldo (Anuario del Seminario de Filología Vasca "Julio de Urquijo", 1992)
This short note deals with the possible etymology of the word azaga, considered an hapax and found in Refranes y Sentencias in 1596. In this collection of proverbs, it was translated into Spanish as ’postrimería’, which has led to the supposition of a romanic (zaga), and ultimately arabic origin. Here, on the contrary, a different reading is proposed: atzaga, with an affricated sibilant, a word noted in Oñati by K. lzagirre (1970), meaning ’a pole placed between two trees on which sheep can scratch themselves’.